Paternalistic Leadership, Polychronicity, and Life Satisfaction of Nurses: The Role of Work-Family Conflict and Family-Work Conflict in Public Sector Hospitals - Gull, Nida; Song, Zhejie; Shi, Rui; Asghar, Muhammad; Rafique, Muhammad Asim; Liu, Yupeng (Frontiers in Psychology, 2021)
Based on the leadership literature, this study investigates how paternalistic leadership (PL) and polychronicity (PC) affect the life satisfaction (LS) of nurses, specifically in public hospitals. Moreover, the mediating role of work-family conflict (WFC) and family-work conflict (FWC) is also assessed the relationships among PL, PC, and LS. The cross-sectional study design is used in this study due to its cost benefits and the convenience of data collection at a single point in time. A survey questionnaire is used to collect data from 226 nurses, and the Partial least squares structural equation modeling (PLS-SEM) technique is used to investigate the proposed model. The findings of this study confirmed that PL and PC have a positive relationship with LS. Furthermore, WFC partially mediated the relationships among PL, PC, and LS. In addition, FWC partially mediated the relationship between PL and LS; the role of FWC in mediating the relationship between PC and LS has been found to be insignificant. Employees with high PC and those whose supervisors show PL behavior become more satisfied with their lives and have relatively low WFC and FWC. In addition, the theoretical and practical implications have also been discussed.